The given polynomial expression is 7x^2 + 42x + 63 = 0.
To factor this expression, we can divide each term by the greatest common factor, which in this case is 7.
Dividing each term by 7, we have:
(x^2 + 6x + 9) = 0.
Now, we can try to factor the quadratic expression (x^2 + 6x + 9) using the product-sum method.
Since the coefficient of the x^2 term is 1, we look for two numbers whose product is 9 and whose sum is 6.
The numbers are 3 and 3, as 3 * 3 = 9 and 3 + 3 = 6.
So, we can factor the quadratic expression as:
(x + 3)(x + 3) = 0.
This can also be written as:
(x + 3)^2 = 0.
To solve for x from this equation, set the expression inside the parentheses equal to zero:
x + 3 = 0.
Subtracting 3 from both sides of the equation, we get:
x = -3.
Therefore, the solution to the polynomial equation 7x^2 + 42x + 63 = 0 is x = -3.
Factor the high-degree polynomial expression 7x^2+ 42x + 63 = 0.
Find x
1 answer